Новое будущее: [сборник рассказов] / составитель Сергей Шикарев - Шикарев Сергей (Эксмо, 2023)
Экземпляры: ЦБ (20230511) / Инвентарный номер: 58142 / Цена: 459.79 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Н 74 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44